Pathophysiology of rhinitis. Lactoferrin and lysozyme in nasal secretions. - Raphael, G D (1989)
The antimicrobial proteins lactoferrin (Lf) and lysozyme (Ly) are invariably found in nasal secretions. To investigate the cellular sources and the secretory control of these nasal proteins in vivo, 34 adult subjects underwent nasal provocation tests with methacholine (MC), histamine (H), and gustatory stimuli. Nasal lavages were collected and analyzed for total protein (TP), albumin (Alb), Lf, and Ly. MC (25 mg), H (1 mg), and gustatory stimuli (spicy foods) all increased the concentrations of TP, Alb, Lf, and Ly. However, when each protein was assessed as a percentage of TP (i.e., Alb% = Alb/TP; Lf% = Lf/TP; Ly% = Ly/TP), MC and gustatory stimuli, which both induce glandular secretion, selectively augmented Lf% and Ly% without changing Alb%, while H, which primarily increases vascular permeability, increased Alb% without significantly affecting Lf% or Ly%. Gel electrophoresis and immunoblotting analysis of nasal secretions demonstrated both Lf and Ly in cholinergically induced secretions. Furthermore, histochemical analyses of nasal turbinate tissue revealed Lf and Ly colocalization within the serous cells of submucosal glands, providing evidence that both proteins are strictly glandular products within the nasal mucosa. Therefore, both Lf and Ly are produced and secreted from the glands, and their secretion may be pharmacologically regulated in attempts to improve host defenses.